2019
DOI: 10.1002/ecy.2597
|View full text |Cite
|
Sign up to set email alerts
|

Differential deployment of sanctioning mechanisms by male and female host trees in a gynodioecious fig–wasp mutualism

Abstract: In some insect nursery pollination mutualisms, plant hosts impose net costs to uncooperative “cheater” symbionts. These “sanctions” promote mutualism stability but their precise adaptive nature remains unclear. In fig–wasp mutualisms host trees (Ficus spp.) are only pollinated by female agaonid wasps whose larvae only use galled fig flowers as food. In actively pollinated systems, if wasps fail to pollinate, sanctions can result via fig abortion, killing all wasp offspring, or by increased offspring mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Decreased rates of abortions with increasing number of foundresses have previously been recorded in F. racemosa (Wang et al 2014) in China as we also found in our study. In a gynodioecious species Ficus hispida, although male trees showed decreased rates of g abortions with increasing foundress numbers, in female trees the effect was less pronounced especially under pollen-free foundress treatments (Zhang et al 2019). This indicates that sanctions differ between sexes, with male trees showing decreased sanctions against wasps since pollinator wasps develop only in syconia of male trees.…”
Section: Discussionmentioning
confidence: 95%
“…Decreased rates of abortions with increasing number of foundresses have previously been recorded in F. racemosa (Wang et al 2014) in China as we also found in our study. In a gynodioecious species Ficus hispida, although male trees showed decreased rates of g abortions with increasing foundress numbers, in female trees the effect was less pronounced especially under pollen-free foundress treatments (Zhang et al 2019). This indicates that sanctions differ between sexes, with male trees showing decreased sanctions against wasps since pollinator wasps develop only in syconia of male trees.…”
Section: Discussionmentioning
confidence: 95%
“…This trend could result from at least four not necessarily mutually independent processes. (a) Foundresses may lay eggs of ever‐reducing genetic viability (sensu Dunn et al, ), (b) of ever‐increasing susceptibility to host plant defences (sensu Dunn et al, ), (c) become depleted of the poison‐sac fluid for effective galling (Martinson et al, ) or (d) investment by trees to figs of variable pollen presence may cause increased larval mortality (Jander & Herre, ; Wang et al, ; Zhang et al, ). There is a lack of data in fig wasps on variation in larval viability, or susceptibility to plant defences, according to when eggs are laid during oviposition bouts, and whether or not gall failure is related directly to poison‐sac fluid reserves.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of data in fig wasps on variation in larval viability, or susceptibility to plant defences, according to when eggs are laid during oviposition bouts, and whether or not gall failure is related directly to poison‐sac fluid reserves. However, a lack of pollen in several fig tree species, including F. racemosa , results in increased pollinator larval mortality (Jander & Herre, ; Jander, Herre, & Simms, ; Wang et al, ; Zhang et al, ). All figs involved in both of our experiments were pollinated but it was unavoidable that each fig received variable amounts of pollen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations